1996
DOI: 10.1590/s0104-79301996000200005
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Scorpionism in Brazil in Recent Years

Abstract: In this paper further information concerning the ecological and biogeographical aspects of scorpionism is presented. Some of the information already outlined in three previous publications(10,14,16) is assessed, and new data given concerning the pattern of distribution presented by Tityus serrulatus in Brazil. Some new ideas are also proposed regarding the possible evolutionary advantages and disadvantages of parthenogenesis versus sexuality in both the short-term and the long-term

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
17

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 9 publications
1
49
1
17
Order By: Relevance
“…Originally described in Pernambuco (Brazil), this species is found in 8 of the 26 states in Brazil, including the island of Fernando de Noronha, State of Pernambuco, Brazil 16 . Tityus stigmurus formerly was found under roofs, among accumulated debris in the exterior areas of residences 3,5 and in cesspits 17 . Control measures rely on chemical insecticides that are not markedly successful 18 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Originally described in Pernambuco (Brazil), this species is found in 8 of the 26 states in Brazil, including the island of Fernando de Noronha, State of Pernambuco, Brazil 16 . Tityus stigmurus formerly was found under roofs, among accumulated debris in the exterior areas of residences 3,5 and in cesspits 17 . Control measures rely on chemical insecticides that are not markedly successful 18 .…”
mentioning
confidence: 98%
“…Of approximately 1,900 known scorpion species in the world 1 , approximately 30 are recognized as potentially dangerous to humans 2 . In South America, scorpions that are dangerous to humans belong to the Buthidae family, particularly those from the genus Tityus CL Koch, 1836 [2][3][4][5][6][7] . Among more than 130 scorpion species described in Brazil 8 , at least 11 harm humans, specifi cally the species Tityus serrulatus Lutz & Mello, 1922), T. bahiensis (Perty, 1833), T. stigmurus (Thorell 1876) and T. obscurus (Lourenço, 2008), which are responsible for serious envenomation or death, particularly in children 9 .…”
mentioning
confidence: 99%
“…The lime paint, with or without some local plants added during preparation, has a repellent action on Centruroides and possibly other scorpions. Brazil -Scorpionism constitutes a public health hazard in many parts of Brazil [151,165,166,167,168], particularly in urban areas. The effects of human activity and environmental changes have allowed the expansion of some species that invade human dwellings and displace less dangerous autochthonous species [168].…”
Section: Scorpions -Basic Epidemiologic Data and Main Control Effortsmentioning
confidence: 99%
“…Brazil -Scorpionism constitutes a public health hazard in many parts of Brazil [151,165,166,167,168], particularly in urban areas. The effects of human activity and environmental changes have allowed the expansion of some species that invade human dwellings and displace less dangerous autochthonous species [168]. In 1988, when a report was being prepared on the number of scorpion attacks in the country, it was found that there had been a significant increase in the number of cases.…”
Section: Scorpions -Basic Epidemiologic Data and Main Control Effortsmentioning
confidence: 99%
“…Among the main causes were urbanization and synantropic habits of Tityus serrulatus (4,5). Another important factor was a new regulation from the Ministry of Health, which required the notification of accidents caused by scorpions.…”
Section: Dear Editormentioning
confidence: 99%